The role of commemoration in the construction of d. Pedro II in the IHGB Journal -1925 (Ágora Journal, 2023)
In 1925, several regions and institutions in the country celebrated the centenary of the birth of D. Pedro II. Among the institutions and periodicals of the press, the Revista do Instituto Histórico e Geográfico (RIHGB) organized a commemorative volume that, by compiling and publishing numerous texts from periodicals, wove a memorial and historiographical narrative with the intention of inscribing the memory/history of the Empire and the Emperor in the Republic. This article intends to investigate the role of this commemoration in the construction of D. Pedro II and the Second Empire, in 1925. For this, the notion of historiographical operation will be adopted as a category of analysis of the narratives that acted in this historical construction of the RIHGB. Based on this research, we present the intentions, impact and quality of this commemoration, which consisted of an undertaking in which it sought to select images, facts, circumstances and values from the monarchical past for that present in the Republic.
Keywords: Celebration; RIHGB; d. Pedro II